2020
DOI: 10.1002/jctb.6310
|View full text |Cite
|
Sign up to set email alerts
|

Leachate recirculation effects on solid‐state anaerobic digestion of Pennisetum hybrid and microbial community analysis

Abstract: BACKGROUND A leach‐bed reactor (LBR) with leachate recirculation is a suitable technology for lignocellulosic biomass anaerobic digestion. In this study, the effect of percolate reflux strategies (continuous recirculation and intermittent recirculation) on methane production from Pennisetum hybrid, a type of energy crop, was investigated using a two‐layered LBR. RESULTS Compared to a solid‐state anaerobic digestion batch test, LBRs with percolate recirculation provide a stable process with a short lag phase by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Qian et al [100] reported that leachate recirculation favored hydrolysis and acidogenesis by its inoculating effect and improved mass transfer, but it also created a washing effect when excessive recirculation was applied, leading to a fast VFA accumulation. Xing et al [89] also reported a detriment in reactor performance when increasing the recirculation frequency of a solid phase reactor treating lignocellulosic biomass (energy crop Pennisetum hybrid). Even if homogenization and biomass wash-out problems are solved, the process still has to deal with the operating conditions.…”
Section: Increasing Reactor Productivity By the Increase In Solid Content And Temperaturementioning
confidence: 99%
“…Qian et al [100] reported that leachate recirculation favored hydrolysis and acidogenesis by its inoculating effect and improved mass transfer, but it also created a washing effect when excessive recirculation was applied, leading to a fast VFA accumulation. Xing et al [89] also reported a detriment in reactor performance when increasing the recirculation frequency of a solid phase reactor treating lignocellulosic biomass (energy crop Pennisetum hybrid). Even if homogenization and biomass wash-out problems are solved, the process still has to deal with the operating conditions.…”
Section: Increasing Reactor Productivity By the Increase In Solid Content And Temperaturementioning
confidence: 99%
“…On the 5th day, the most abundant archaeal were Methanosarcina , Methanothrix , Methanomassiliicoccus , Methanobacterium , and Methanoculleus in the control experiment. Methanosarcina and Methanothrix belonged to aceticlastic methanogen, and Methanobacterium , Methanoculleus , and Methanomassiliicoccus were hydrogenotrophic archaea 28,41,42 . Both aceticlastic methanogen (25.91%) and hydrogenotrophic archaea (27.48%) were the predominant methanogens in the control experiment.…”
Section: Resultsmentioning
confidence: 95%
“…Microbial DNA was extracted using a E.Z.N.A™ Mag‐Bind Soil DNA Kit; results were quantified using a Qubit 3.0 DNA test kit. Primers (341F and 805R) were used to amplify the V3‐V4 hypervariable region using a polymerase chain reaction (PCR) 28 . Two rounds and three rounds of PCR were used to amplify 16S rRNA genes for bacteria and archaea, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these authors pointed out that when recirculation was excessive, then a negative outcome was observed because it then caused microbial biomass washout and VFA accumulation. Xing et al [54] also evaluated the recirculation of leachate, treating lignocellulosic biomass (Pennisetum hybrid) as a substrate. They found a similar detriment in reactor performance when the frequency of recirculation was increased.…”
Section: Operating Conditions and Leachate Bed Configurationmentioning
confidence: 99%